PENGARUH EKSTRAK DAUN LEGUNDI (VITEX TRIFOLIA, L) DAN RIMPANG TEMULAWAK (CURCUMA XANTHORRHIZA, ROXB) TERHADAP KADAR IGE TOTAL SERUM & EOSINOFIL USAPAN MUKOSA HIDUNG PENDERITA RINITIS ALERGI - , WIWIN HERDWIANI.,S.F.,APT, Prof. dr. Zullies Ikawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The combination between Legundi leaves and curcumae rhizomes extract has been reported to have suppression effects on cutaneous anaphylactic reaction and no toxic effects have been noted in female wistar rats. Phase I Clinical Assay showed that the dosages of 1500mg/day and 4500mg/day are safe and tolerable. The aims of this research are to examine whether there is an effect of the combination between Legundi leaves and curcumae rhizhome for both dosages (1500mg/day and 4500mg/day) on (1) total IgE levels (2) nasal swab eosinophil in allergic rhinitis patients. The design of the study is randomized double-blind placebo-controlled. Allergic rhinitis patients (N=33) who met the inclusion-exclusion criteria were divided into three groups : placebo, 1500mg/day, 4500mg/day of combination. Each of the medicine is to be taken for every 8 hours for 14 days. Serum IgE and nasal swab eosinophil were measured before and after ( the -15th day) treatment. The results of IgE levels research were analyzed with paired t-test and anova (p = 0.005) while the diagnosis based on the levels of nasal swab eosinophil were analyzed by Chi-square test (p = 0.005). The study was approved by the etics committee of the Commission on Human Biomedical Recearch Faculty of Gadjah Mada University. The results showed that the combination of legundi leaves and curcumae rhizome extract of 4500mg/day has the tendency to decrease the levels of total IgE. It has significant difference compared to 1500mg/day (p = 0.014). The group of 1500mg/day and 4500mg/day have no significant difference in the diagose compared to placebo based on nasal swab eosinophil (p = 1.000).